Epigenetic Mechanisms Are Critical for the Regulation of WUSCHEL Expression in Floral Meristems - Cao, Xiuwei (Plant Physiol, 2015)
The floral meristem (FM), which develops from the inflorescence meristem upon completion of the floral transition, terminates after producing a defined number of floral organs. This is in contrast to the shoot apical meristem, which is active throughout the entire life span of plants. WUSCHEL (WUS) encodes a homeodomain-containing protein and plays a critical role in shoot apical meristem, inflorescence meristem, and FM establishment and maintenance as well as FM determinacy. Although many genes have been implicated in FM determinacy through the regulation of WUS expression, precisely how these genes are coordinated to regulate WUS and consequently dictate FM fate remains unclear. Emerging lines of evidence indicate that epigenetic mechanisms, such as histone modification, chromatin remodeling, noncoding RNAs, and DNA methylation, play vital roles in meristem maintenance and termination. Here, recent findings demonstrating the involvement of the epigenetic network in the regulation of WUS expression in the context of FM determinacy are summarized and discussed.